علاقة المسلسلات الأجنبية(مسلسل نور التركي) بقيم المراهق - عليوش نجمة (University of Eloued جامعة الوادي, 2024)
تبحث هذه الورقة البحثية عن وجود علاقة بين المسلسلات الأجنبية وقيم المراهق من عدمه، وقد اخترنا مسلسل نور التركي نموذجا، للشهرة الكبيرة التي عرفها في المجتمعات العربية، ونسب المشاهدة العالية التي حققها أثناء عرضه، حيث دلت الإحصاءات على أن متابعيه كانوا من مختلف شرائح وفئات المجتمع الجزائري والعربي، كما كان موضع جدل كبير في مختلف الأوساط، بسبب محتواه الذي أحدث ضجة ليتحول بحق إلى ظاهرة، كما كان مختلفا عن القيم والثقافة العربية الإسلامية، وكانت الدراسة الميدانية في ثانوية بوقيقز عمار بمدينة القل بسكيكدة، لنبحث عن علاقة المسلسل بقيم المراهقين لحساسية المرحلة العمرية التي يمرون بها، وتأكدنا من اختيار العينة من التلاميذ الذين شاهدوا المسلسل بجميع حلقاته، وركزنا في هذه الدراسة على تصنيفات معينة من القيم وهي: القيم الاجتماعية، والقيم الدينية، وانعكاسها على سلوكياتهم من عدمه، واستخدمنا في دراستنا المنهج الوصفي لتحليل وتفسير المعطيات الكمية، كما استعنا بأداة تحليل المضمون لتحليل مسلسل نور التركي محور الدراسة، لنتوصل إلى مجموعة من النتائج. Abstract : This research paper examines whether or not there is a relationship between foreign series and adolescent values. We chose the Turkish series Nour as a model, due to the great fame it gained in Arab societies, and the high viewership rates it achieved during its broadcast, as statistics indicated that its followers were from various segments and groups of society. Algerian and Arab, and it was the subject of great controversy in various circles, because of its content, which caused a stir and truly turned into a phenomenon, as it was different from Arab-Islamic values and culture. The field study was in Buqaqiz Ammar High School in the city of Al-Qal, Skikda, to search for the relationship of the series to the values of teenagers due to the sensitivity of the stage. The age they are experiencing, and we made sure to choose the sample from students who watched the series with all its episodes via YouTube, and the study sample amounted to 60 individuals, and in this study we focused on certain classifications of values, namely: social values, religious values, and their reflection on their behavior, and in our study we used the method Descriptive analysis and interpretation of quantitative data. We also used the content analysis tool to analyze the Turkish series Nour, the focus of the study, to reach a set of results, the most notable of which is that the Turkish series Nour did not cause a change in the values of the sample members.
دراسة ميدانية على عينة من تلاميذ المرحلة الثانوية بالقل سكيكدة
Keywords: مسلسل نور التركي; القيم; المراهق; series; Value; Adolescence; Turkish serial Nour